Update on the role of R2R3-MYBs in the regulation of glucosinolates upon sulfur deficiency - Frerigmann, Henning; Gigolashvili, Tamara (Frontiers in Plant Science, 2014)
To balance the flux of sulfur (S) into glucosinolates (GSL) and primary metabolites plants exploit various regulatory mechanisms particularly important upon S deficiency (–S). The role of MYB34, MYB51 and MYB122, controlling the production of indolic glucosinolates (IGs) and of MYB28, MYB29 and MYB76 regulating the biosynthesis of aliphatic glucosinolates (AGs) in Arabidopsis thaliana has not been fully addressed at –S conditions yet. We show that the decline in the concentrations of GSL during S depletion does not coincide with the globally decreased transcription of R2R3-MYBs. Whereas the levels of GSL are diminished, the expression of MYB34, MYB51, MYB122 and MYB28 is hardly changed in early phase of S limitation. Furthermore, the mRNA levels of these MYBs start to raise under prolonged S starvation. In parallel, we found that SLIM1 can downregulate the MYBs in vitro as demonstrated in trans-activation assays in cultured Arabidopsis cells with SLIM1 as effector and ProMYB51:uidA as a reporter construct. However, in vivo, only the mRNA of MYB29 and MYB76 correlated with the levels of GSL at –S. We propose that the negative effect of SLIM1 on GSL regulatory genes can be overridden by a “low GSL signal” inducing the transcription of MYBs in a feedback regulatory loop. In accordance with this hypothesis, the expression of MYB34, MYB51, MYB122 and CYP83B1 was further induced in cyp79b2 cyp79b3 mutant exposed to –S conditions vs cyp79b2 cyp79b3 plants grown on control medium. In addition, the possible role of MYBs in the regulation of essential S assimilation enzymes, in the regulation of GSL biosynthesis upon accelerated termination of life cycles, in the mobilisation of auxin and lateral root formation at S deficiency is discussed.